Lymph-node metastasis from gastric adenocarcinoma in a patient bearing a germ line missense variant MSH2 c.1808A > T (Asp603Val) responds to the immune checkpoint inhibitor pembrolizumab. (8th December 2022) - Kiyomiya, Miki; Fukuda, Koji; Shimazu, Kazuhiro; Yoshida, Taichi; Taguchi, Daiki; Shinozaki, Hanae; Nanjyo, Hiroshi; Shibata, Hiroyuki
Abstract: We report the sensitivity of immune checkpoint inhibitors for tumors developing in a patient bearing the MSH2 c.1808A > T (Asp603Val) variant belonging to a pedigree of Lynch syndrome. This variant was previously thought to be of unknown significance, but we recently found that this missense mutation was likely pathogenic. At that time, there were no active members with malignancies that could be treated with chemotherapy. Thereafter, an 81-year-old woman bearing this variant, who was a cousin of the proband of this family, had multiple lymph node metastases from her resected gastric cancer. An immune checkpoint inhibitor, pembrolizumab, an anti-PD-1 antibody, was used to treat these tumors. After 3 months of treatment, almost all tumors disappeared, and elevated CA19–9 levels normalized. She survives over 15 months safely. It was indicated that the tumors bearing this germline variant were sensitive to pembrolizumab. This observation suggests that an MSH2 c.1808A > T (Asp603Val) variant induces mismatch repair deficiency, resulting in sensitization to immune checkpoint inhibition. Abstract : The lymph node metastases in a Lynch syndrome patient bearing an MSH2 c.1808A > T (Asp603Val) missense variant are sensitive to pembrolizumab, an immune checkpoint inhibitor due to its mismatch repair deficiency.